Modulation of Litter Decomposition by the Soil Microbial Food Web Under Influence of Land Use Change - Heijboer, Amber; de Ruiter, Peter C.; Bodelier, Paul L. E.; Kowalchuk, George A. (Frontiers in Microbiology, 2018)
Soil microbial communities modulate soil organic matter (SOM) dynamics by catalyzing litter decomposition. However, our understanding of how litter-derived carbon (C) flows through the microbial portion of the soil food web is far from comprehensive. This information is necessary to facilitate reliable predictions of soil C cycling and sequestration in response to a changing environment such as land use change in the form of agricultural abandonment. To examine the flow of litter-derived C through the soil microbial food web and it’s response to land use change, we carried out an incubation experiment with soils from six fields; three recently abandoned and three long term abandoned fields. In these soils, the fate of 13C-labeled plant litter was followed by analyzing phospholipid fatty acids (PLFA) over a period of 56 days. The litter-amended soils were sampled over time to measure 13CO2 and mineral N dynamics. Microbial 13C-incorporation patterns revealed a clear succession of microbial groups during litter decomposition. Fungi were first to incorporate 13C-label, followed by G- bacteria, G+ bacteria, actinomycetes and micro-fauna. The order in which various microbial groups responded to litter decomposition was similar across all the fields examined, with no clear distinction between recent and long-term abandoned soils. Although the microbial biomass was initially higher in long-term abandoned soils, the net amount of 13C-labeled litter that was incorporated by the soil microbial community was ultimately comparable between recent and long-term abandoned fields. In relative terms, this means there was a higher efficiency of litter-derived 13C-incorporation in recent abandoned soil microbial communities compared to long-term abandoned soils, most likely due to a net shift from SOM-derived C towards root-derived C input in the soil microbial food web following land-abandonment.